The impact of COVID‐19 vaccine on sperm quality. Issue 1 (26th February 2022) - Barda, Shimi; Laskov, Ido; Grisaru, Dan; Lehavi, Ofer; Kleiman, Sandra; Wenkert, Atalia; Azem, Foad; Hauser, Ron; Michaan, Nadav
Abstract: Objective: To examine the effect of the BNT162b, mRNA, SARS‐CoV‐2 virus vaccine on sperm quality. Methods: This was a prospective cohort study conducted on sperm donors at the sperm bank of a tertiary, university affiliated medical center. All sperm donors donated sperm repeatedly and the average sperm parameters of all available samples were compared before and after receiving the SARS‐CoV‐2 vaccine. Each donor served as his own control. For all participants, at‐least one sperm sample was received 72 days after completing the second vaccine. Main outcome measures included total sperm count, total motile count and percent of motile sperm. Results: A total of 898 sperm samples from 33 sperm donors that were vaccinated with the Pfizer BNT162b, mRNA, SARS‐CoV‐2 virus vaccine were analyzed, 425 samples were received before the vaccine, while 473 samples were received after vaccination. Total sperm count and total motile count increased after the second vaccine compared to samples before vaccination. Percent of motile sperm did not change after vaccine. Conclusion: The Pfizer BNT162b, SARS‐CoV‐2 vaccine has no deleterious effect on sperm quality. Patients and physicians should be counseled accordingly. Abstract : The Pfizer BNT162b, SARS‐CoV‐2 vaccine has no deleterious effect on sperm quality.